Support system for local water planning: flood detections using remote sensing in Honduras - Pérez Escobar, Jorge Andres; Paz Garcia, Paula; Tello Dagua, Jhon Jairo; Reymondin, Louis (2022)
This dataset contains spatial surfaces with the number of flooding events detected per year using satellite imagery in Honduras between 2017 and 2022. In addition, the accumulated annual flood events detected for the analyzed six-year period is also published. They are classified into the following three (3) classes according to the number of events detected: